HOW BIG ARE THE EMPLOYMENT EFFECTS OF MICROLOANS? EVIDENCE FROM A CASE STUDY IN LATVIA - BALDI, Guido; ŠIPILOVA, Viktorija (Theoretical and Practical Research in Economic Fields; Vol 5 No 1 (2014): TPREF, Volume V, Issue 1(9), Summer 2014DO - 10.14505/tpref.v5.1(9).02, 2016)
Microloans to small and medium-sized enterprises have become popular in many countries. However, evidence on the economic and social impact of microfinance is scarce. In an attempt to partly fill this gap, this paper looks at a case study and analyzes the economic impacts of the microloan programme of the Latvian development bank Hipoteku Banka. In our analysis, we focus on the following questions: Did the microloan programme increase employment within the supported firms? And was it able to contribute to the economic development of rural areas and the decrease of economic inequalities across regions? We find that the firms that were granted a loan from Hipoteku Banka on average considerably increased their employment during the loan period, as well as the microloan programme made a successful contribution to the economic development of rural regions in Latvia.